Empowered to Break the Silence: Applying Self-Determination Theory to Employee Silence - Dong Ju (Frontiers in Psychology, 2019)
The paper studies how leaders can break employee silence. Drawing upon self-determination theory, we argue that empowering leadership can activate employees’ intrinsic motivation such that employees are more willing to break the silence at work; furthermore, the effect is stronger when employees have high (vis-à-vis low) levels of job autonomy. We collected time-lagged and multi-source data in a large company to test our hypotheses. The results show that intrinsic motivation mediates the relationship between empowering leadership and employee silence. That is, empowering leadership can reduce employee silence through enhancing their intrinsic motivation. Furthermore, this mediation effect will be stronger when employees have high levels of job autonomy. This paper contributes to the literature on leadership, employee silence, and job design characteristics.